Development of the Portable Shake Table for Simulating Building Characteristic under Earthquake Condition - Suluch, Munarus; Adhim, Fauzi Imaduddin; Priananda, Ciptian Weried; Rahayu, Lucky Putri; Kurnianto, Mahfud; Cantona, Singgih; Jauhari, Moh. (IPTEK Journal of Proceedings Series, 2019)
In the last few decades, massive earthquakes, which can damage many homes and buildings, have often occurred. To slow down or prevent damage from earthquakes, various technologies are needed. From this technology, simulators of ground motion from earthquakes can be used to remind people of the dangers of earthquakes. This paper introduces a portable earthquake simulator to simulate two-dimensional ground motion from an earthquake. Focusing on the design concept, structure, and features of this new simulator, the author discusses its implementation and verifies its feasibility with the results of the initial experiments.